Comparison of changes in shoulder functions between biceps tenotomy and tenodesis in an animal model - Chih-Kai Hong; Ming-Long Yeh; Chih-Hsun Chang; Florence L. Chiang; I-Ming Jou; Ping-Hui Wang; Wei-Ren Su (Elsevier, 2019)
Objectives: Tenotomy and tenodesis of the long head of biceps tendon are effective pain-relieving treatments. However, there is no consensus on the functional outcome after these surgical procedures. We hypothesized that there would be no difference in ambulation parameters after recovery from the surgery between rats that underwent tenotomy versus tenodesis procedures. Methods: Twenty-four New Zealand rats were used and randomly divided into three groups. Each group received one of the following surgeries: tenotomy, tenodesis, and sham operation. A video-based walking track system was applied for gait analysis at day −1, 1, 3, 5, 7, 14 and 21 for each rat. Temporal and spatial parameters were obtained, and asymmetric index was calculated for each parameter. Results: Compared to the tenotomy and sham-operated groups, the rats in the tenodesis group had shorter stance phase, longer swing time, longer step length, smaller paw length, smaller intermediary toe-spread length, smaller toe-spread length, and larger foot angle right after the tenodesis procedure. After day 14, all parameters were equivalent to those of the sham-operated group. At the end of the study, there were no functional changes found in tenotomy and tenodesis groups compared with the sham-operated group and preoperative status. Conclusion: Transient functional alterations in temporal and spatial parameters are found after tenotomy and tenodesis in a rat model. The functional changes in the tenodesis group existed for a longer period than in tenotomy group; however, and all parameters showed no significant differences when compared with the sham group at the conclusion of the study. Keywords: Long head of biceps tendon, Tenotomy, Tenodesis, Gait analysis, Functional outcome, Asymmetric index